A CONCEPTUAL FRAMEWORK FOR ADAPTIVE ENGLISH LEARNING IN VIETNAM USING PERTURBATION LEARNER MODEL - NGUYEN , VIET DUNG (2013)
Earlier research has proved that adaptive learning is an advanced educational method applicable to a variety of educational and training models to enhance the effectiveness and efficiency in teaching and learning. The idea behind adaptive learning is agreed to be the absolute utilization of explicit learner models - created and constantly updated through a process called user modeling - capable of managing users' information and automatically adapting the presentation of learning content and material according to the users' responses and progress when interacting with the learning system.